Pengaruh Keyakinan dan Kepercayaan Teknologi Terhadap Minat Penggunaan Internet Banking Di Malang: Theory of Reason Action yang Direduksi - Mardiyanti, Sofiana; Purnomosidhi, Bambang (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This research aimed to examine the effect of technology self efficacy and trust in technology to intention use internet banking in the Malang using models theory of reaction action and research of model reduction Selvan et al, (2011). Amount of the sample is 138 bank customers used internet banking. Results of the analysis for this model shows that intention to use internet banking is influenced by technology self efficacy mediated by attitudes toward internet banking, overall attitude toward service self technologies, and trust in technology. Positive feelings towards service self technologies and internet banking will indicate how large the intention of someone to use internet banking. The self efficacy and trust of high technology can foster positive feelings towards service self technologies and internet banking so as to encourage the intention of someone to either using the internet bangking. The results of this research proves that intention to use internet banking can be described using the theory of reason action. Therefore, it is important to the banker authorities to note the level of trust and self efficacy in the internet banking technology implements as means of payment so as to encourage the intention of its customers to use internet banking. Keywords: Theory of Reaction Action (TRA), internet banking, intention, efficacy, trust, and attitude.